Knowledge Transfer Based Local Wisdom by Learning Method Buddy Program In District Bengkayang - Priska Vasantan; Helena Anggraeni Tjon (International Journal of Multi Discipline Science, 2018)
Knowledge transfer is one of knowledge management. Knowledge transfer based on local wisdom is very helpful in learning methods in schools and universities, especially at the outermost district in Indonesia. This study is research in one school that located in Bengkayang which is one of the districts the outermost in Indonesia that the student has behind from academic, computer ability, Indonesian language, English language, etc. Therefore this study aims to show the importance of knowledge transfer based on local wisdom in learning in this school. The aim of this research is to show that knowledge transfer based on local wisdom is very helpful in learning method especially at district Bengkayang, one of the outermost district in Indonesia.